Ruck frequency as a predictor of success in the 2007 Rugby World Cup tournament - van Rooyen, M. K.; Diedrick, E.; Noakes, T. D. (International Journal of Performance Analysis in Sport, 2010)
An evaluation of the 2007 Rugby World Cup was conducted to establish if ruck occurrence could predict successful performance. These data were compared with the 6 Nations and Tri Nations competitions of 2007. There were 117 (range 65 - 172) rucks per match. The knockout stages had a greater number of rucks per game (121 range 71-164) than the pool stages (116 range 65-172). 66% of rucks occurred in the midfield zones, 28% in the attacking and 7% in the defensive zones. Comparisons with the 6 Nations and Tri Nations revealed that there were 20% fewer rucks during World Cup matches. Matches during the pool stages were won (58%) by teams with the highest number of rucks. This was also observed during the 6 Nations and the Tri Nations. In the knockout stages the team with the fewest rucks won 100% of the matches. These data suggest that during International rugby competitions and pool stages of a World Cup, the greater the number of rucks that a team creates, the more likely it is to win the match. This strategy was not effective during the knockout stages of the Rugby World Cup; here the avoidance of rucking was associated with success.